Growth-Independent Regulation of CLN3 mRNA Levels by Nutrients in Saccharomyces cerevisiae - Parviz, Fereshteh (American Society for Microbiology, 1998)
Saccharomyces cerevisiae cells regulate progress through the G(1) phase of the cell cycle in response to nutrients, moving quickly through G(1) in rich medium and slowly in poor medium. Recent work has shown that the levels of Cln3 protein, a G(1) cyclin, are low in cells growing in poor medium and high in cells growing rapidly in rich medium, consistent with the previously recognized role of Cln3 in promoting passage through Start. Cln3 protein levels appear to be regulated both transcriptionally and posttranscriptionally. We have worked to define the nutrient signals that regulate CLN3 mRNA levels. We find that CLN3 mRNA levels are high during log-phase growth in glucose medium, low in postdiauxic cells growing on ethanol, and slightly lower still in cells in stationary phase. CLN3 mRNA levels are induced by glucose in a process that involves transcriptional control, requires metabolism of the glucose, and is independent of the Ras-cyclic AMP pathway. CLN3 mRNA levels are also positively regulated by nitrogen sources, but phosphorus and sulfur limitation do not affect CLN3 message levels.